Investigations of Electrostatic and Ionized Fields Analysis for Dual-Electrode System - Mohamed A. Abouelatta; Abdelhadi R. Salama; A. M. Omar; S. A. Ward (Institute of Advanced Engineering and Science, 2016)
The paper presents the computation and measurement of electric field, in both electrostatic as well as ionized case, for dual electrode system intended for electrostatic applications. The dual electrode system consists of an ionizing and non-ionizing electrode have the same voltage and facing a grounded collecting plate. The charge simulation method (CSM) coupled with genetic algorithms (GAs) and method of characteristic (MOC) is applied to compute the electrostatic field and the ionized field respectively. The influence of dual system parameters such as ionized wire diameter and inter electrode distances on the profile of the electrostatic field on the collecting plate and on the surface of the ionizing wire has been studied. The measurements of the ionized electric field, current-voltage characteristics and ion current density profiles are implemented using the technique of the linear biased probe. An experimental setup is constructed to model the present electrode arrangement. The measurements are carried out for ionized wire of diameter 0.25 and 0.5mm. The computed results are found to be in good agreement with experiments.